A study of the prevalence of post-partum depression in a secondary care hospital in Dimapur, Nagaland, Northeast-India - Singh, Ravi; Jamir, Bendangtoshi; Vashum, Hongreiwon (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Post Partum Depression (PPD) is a very common mental health issue emerging in pregnant woman worldwide. This research tries to find out prevalence of post-partum depression and factors leading to its development. Methods: A structured interview was conducted involving 178 pregnant women of age >18 years. During their intra-natal period they were given an EPDS questionnaire and then after 2 weeks they were reassessed through telephonic interview. The results of two EPDS scores and variables was obtained on paper and analysed on Microsoft Excel. Results: This study shows a prevalence of PPD to be 54.49%. It was also found in this study that Post-Partum Depression is very closely associated with history of miscarriage in previous pregnancies (p=0.042). Conclusions: Prevalence of PPD is very high in Northeast India specially in urban areas. This study included in-patients and found 54.49% prevalence of PPD. Miscarriage being strongly associated.